THE USE OF NUDGES IN THE FIGHT AGAINST INFORMALITY IN BRAZIL (Revista Inclusiones, 2021)
The article aims to study the fight against informality in Brazil, suggesting the use of the behavioral economics tool called nudge by the public power. The main objective is to expand the debate on the use of the new mechanisms of economic theory to try to combat the problem of informality in the Brazilian labor market. The relevance of the theme of combating informality has important repercussions on the worker's life, on the organization of companies and on the responsibilities of the public authorities. To demonstrate this importance, it was chosen the social security aspect of the problem by collecting the existing data and highlighting the consequences of informality for the worker and for the State. The conceptual bases of the application of nudges and the cognitive biases of the cascade of availability and intertemporal discount were presented. The questioning of the multiplicity of models of job attachment made available to the citizen was presented, which, instead of reaching the intended objective of making relations more flexible, leading to better levels of formality, can make the choices more complex. Finally, it was concluded by the convenience of the use by architects of governmental choices of a better structure and availability of information that makes the consequences of their choices for themselves and for society accessible to citizens, inducing employers and workers to make the decisions with best results for the country's social objectives.